Viscero‐visceral hyperalgesia in dysmenorrhoea plus previous urinary calculosis: Role of myofascial trigger points and their injection treatment in the referred area. (4th March 2020) - Costantini, Raffaele; Affaitati, Giannapia; Fiordaliso, Michele; Giamberardino, Maria Adele
Abstract: Background: Women with dysmenorrhoea plus symptomatic urinary calculosis experience enhanced pain and referred muscle hyperalgesia from both conditions than women with one condition only (viscero‐visceral hyperalgesia). The study aimed at verifying if enhanced dysmenorrhoea persists after urinary stone elimination in comorbid women and if local anaesthetic inactivation of myofascial trigger points (TrPs) in the lumbar area (of urinary pain referral) also relieves dysmenorrhoea. Methods: Thirty‐one women with dysmenorrhoea plus previous urinary calculosis (Dys+PrCal) and lumbar TrPs, and 33 women with dysmenorrhoea without calculosis (Dys) underwent a 1‐year assessment of menstrual pain and muscle hyperalgesia in the uterus‐referred area (electrical pain threshold measurement in rectus abdominis, compared with thresholds of 33 healthy controls). At the end of the year, 16 comorbid patients underwent inactivation of TrPs through anaesthetic injections, whereas the remaining 12 received no TrP treatment. Both groups were monitored for another year at the end of which thresholds were re‐measured. Results: In year1, Dys+PrCal presented significantly more painful menstrual cycles and lower abdominal thresholds than Dys, thresholds of both groups being significantly lower than normal ( p  < .001). Anaesthetic treatment versus no treatment of the lumbar TrP significantly reduced the number of painful cycles during year2 and significantly increased the abdominal thresholds ( p  < .0001). Conclusion: Viscero‐visceral hyperalgesia between uterus and urinary tract may persist after stone elimination due to nociceptive inputs from TrPs in the referred urinary area, since TrPs treatment effectively reverses the enhanced menstrual symptoms. The procedure could represent an integral part of the management protocol in these conditions. Significance: A past pain process from an internal organ can continue enhancing pain expression from a painful disease in another neuromerically connected organ (viscero‐visceral hyperalgesia) if secondary myofascial trigger points (TrPs) developed in the referred area at the time of the previous visceral disease. Inactivation of these TrPs reverts the enhancement. Assessment and treatment of TrPs in referred areas from past visceral pain conditions should be systematically carried out to better control pain from current diseases in other viscera.